Передача інтерференційної картини крізь оптичний тракт із нестаціонарними фазовими перешкодами - Медвідь, Наталія Вікторівна; Бікман, Павло Олександрович; Держипольська, Людмила (My University, 2013)
У статті досліджено можливість використання високоенергетичних багатомодових світловодних джгутів при проведенні інтерферометричних досліджень у важкодоступних місцях. Визначено межі припустимих змін стану джгутів під час експерименту, а також можливість виключення їх впливу за рахунок схемних модифікацій в інтерферометрі. In this paper we study the possibility of using fiber optic harnesses in conducting the interferometric transmission of information from remote and dangerous places. This problem is restricted to the investigation of mismatch in distribution of fields in the individual optical fibers included in the harness when the wiring changes occur during the experiment. For example, the bending of optical fibers in a bundle can significantly change the modal composition of the field in each individual fiber. A method of holographic interferometry has been used during the study. Therefore, the disturbance in the wiring could lead to changes in the distribution of the field in the plane of the recording of the first and second gollogramm. Strong perturbations significantly reduce the contrast of interference lines. Therefore, a correlation technique has been developed for comparing the distributions of the field at the output end of the rope in two of its different states. The field images were subtracted one from another pixel by pixel. The average difference is a quantitative measure of admissible perturbations. It is in range of 5 relative units (r.u.) to 18—25 (r.u.) when interferometric stripes disappear. Also an analysis of possibility to eliminate the influence of disturbances in harness was made. A method for the simultaneous transmission of the signal and reference beams through the wiring using the Gabor scheme has been proposed. The resulting picture has been processed to select the desired image of interferometric lines.
Keywords: фазові перешкоди оптичного тракту; багатомодовий світловодний джгут; голографічна інтерферометрія; phase distortions in the optical path; multimode fiber optic harness; holographic interferometry; кафедра фізики та професійної безпеки